Satellite-based estimates of long-term exposure to fine particles and association with mortality in elderly Hong Kong residents - Wong, C; Lai, H; Lee, S; Hedley, A; Lam, T; Tsang, H; Thomas, G; Lam, K; Chan, P; Yang, L; Lau, A; Ayres, J (National Institute of Environmental Health Sciences, 2015)
Background: A limited number of studies on long-term effects of particulate matter with aerodynamic diameter <2.5 µm (PM2.5) on health suggest it can be an important cause of morbidity and mortality. In Asia where air quality is poor and deteriorating, local data on longterm effects of PM2.5 to support policy on air quality management are scarce. Objectives: We assessed long-term effects of PM2.5 on the mortality in a single Asian city. Methods: We followed up for 10–13 years a cohort of 66,820 participants aged ≥65 who were enrolled and interviewed in all 18 Elderly Health Centres of the Department of Health, Hong Kong in 1998–2001. Their residential addresses were geo-coded into x- and y- coordinates and their proxy exposures to PM2.5 at their addresses in 1×1 km grids were estimated from the US National Aeronautics and Space Administration (NASA) satellite data. We used Cox regression models to calculate hazard ratios (HRs) of mortality associated with PM2.5. Results: Mortality HRs per 10-µg/m3 increase in PM2.5 were 1.14 (95% CI: 1.07, 1.22) for all natural causes, 1.22 (95% CI: 1.08, 1.39) for cardiovascular causes, 1.42 (95% CI: 1.16, 1.73) for ischemic heart disease, 1.24 (95% CI: 1.00, 1.53) for cerebrovascular disease, and 1.05 (95% CI: 0.90, 1.22) for respiratory causes. Conclusions: Our methods in using NASA satellite data provide a readily accessible and affordable approach to estimation of a sufficient range of individual PM2.5 exposures in a single city. This approach can expand the capacity to conduct environmental accountability studies in areas with few measurements of fine particles.